Battery current collector, preparation method of battery current collector, negative-electrode-free sodium ion battery and preparation method of negative-electrode-free sodium ion battery
By coating the titanium-tungsten alloy gradient coating on the surface of the aluminum foil substrate without anode sodium ion battery, problems such as uneven sodium ion deposition and volume expansion are solved, and the high energy density and long life of sodium ion batteries are achieved.
Patent Information
- Application Number
- CN202510398953.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-04-01
AI Technical Summary
In negative-electrode sodium ion batteries, traditional aluminum foil current collectors lead to uneven sodium ion deposition, which easily triggers dendrite growth and interface side reactions, and the alloying modification strategy has problems of severe volume expansion and poor chemical stability.
A gradient coating of titanium and tungsten alloy is coated on the surface of the aluminum foil substrate. The coating is distributed in gradient components. The electron distribution on the surface of the alloy is regulated through the synergistic action of titanium and tungsten, forming highly sodium-philic active sites, reducing sodium nucleation overpotential, and preparing the coating through magnetron sputtering or plasma enhanced chemical vapor deposition technology.
Significantly reduce the sodium nucleation overpotential, achieve dense and dendrite-free sodium deposition behavior, improve the safety and cycle stability of the battery, solve the problems of volume expansion and chemical stability, extend the cycle life of the battery and improve safety.
Smart Images

Figure CN119905600A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a battery current collector and a preparation method thereof, and a negative electrode-free sodium ion battery and a preparation method thereof. Background Art
[0002] With the rapid development of the new energy industry, the safety, energy density and resource sustainability of battery technology have become key factors in promoting the upgrading of the industry. Traditional liquid lithium-ion batteries use flammable organic electrolytes, which have inherent defects such as high risk of thermal runaway and limited energy density improvement. In addition, the global reserves of lithium resources are limited (about 0.0065% in the earth's crust) and unevenly distributed, resulting in a fragile supply chain, making it difficult to meet the urgent demand for high-performance batteries in electric vehicles, energy storage and other fields.
[0003] As an emerging battery technology, anode-free sodium-ion batteries are considered an important direction to break through the bottleneck of sodium battery industrialization due to their advantages such as no need to preload metal sodium anode and simplified process. However, the core challenge of anode-free sodium-ion batteries lies in how to achieve efficient and uniform deposition and stable circulation of sodium metal on the surface of the current collector.
[0004] At present, the traditional aluminum foil current collector has low surface energy, which leads to uneven sodium ion deposition, easily causing dendrite growth, interface side reactions and rapid capacity decay. In order to solve these problems, researchers have proposed alloying modification strategies, such as aluminum-based alloy coatings, to reduce the sodium nucleation overpotential. However, these alloying coatings are accompanied by drastic volume expansion during the alloying / de-alloying process (such as Na-Al alloying volume change >200%), which can easily cause the current collector structure to pulverize and the solid electrolyte interface (SEI) film to rupture repeatedly, seriously restricting the cycle life of the battery.
[0005] In addition, the high reactivity of metallic sodium makes conventional coating materials (such as copper and nickel) susceptible to chemical corrosion or phase change with sodium during long-term cycles, further exacerbating the increase in interfacial impedance and the degradation of electrochemical performance.
[0006] The prior art has the following main disadvantages for the negative electrode current collector of the negative electrode-free sodium ion battery: Uneven sodium deposition: The traditional aluminum foil current collector has low surface energy, which leads to uneven sodium ion deposition and easily induces dendrite growth, affecting the safety and cycle life of the battery.
[0007] Significant volume expansion: Existing alloying modification strategies (such as aluminum-based alloy coatings) are accompanied by dramatic volume expansion during the alloying / de-alloying process, which can easily cause the collector structure to become powdery, severely restricting the cycle life of the battery.
[0008] Poor chemical stability: The high reactivity of metallic sodium makes conventional coating materials susceptible to chemical corrosion or phase change with sodium during long-term cycles, resulting in increased interfacial impedance and degradation of electrochemical performance.
[0009] It is necessary to propose a solution to solve the shortcomings of the above-mentioned existing technologies and promote the leapfrog development of negative electrode-free sodium battery technology towards high energy density and long life. Summary of the invention
[0010] In view of the problems existing in the prior art, the present invention provides a negative electrode-free sodium ion battery current collector based on a titanium-tungsten alloy gradient coating, comprising: an aluminum foil substrate, and a titanium-tungsten alloy coating coated on the surface of the aluminum foil substrate, wherein the titanium-tungsten alloy coating has a gradient component distribution.
[0011] Preferably, the titanium-tungsten alloy coating comprises a titanium-rich layer, a transition layer and a tungsten-rich layer stacked in sequence from an aluminum foil substrate outward; the ratio of titanium atoms to tungsten atoms in the titanium-rich layer, the transition layer and the tungsten-rich layer decreases in sequence to form the gradient component distribution.
[0012] Preferably, the transition layer includes multiple subdivided layers, and the ratio of the number of titanium atoms to tungsten atoms in the subdivided layers gradually changes from 3:1 to 1:1 in levels.
[0013] Preferably, the ratio of the number of titanium atoms to tungsten atoms in the titanium-tungsten alloy coating as a whole is in the range of 1:1 to 3:1.
[0014] Preferably, the ratio of the thickness of the titanium-rich layer to the thickness of the tungsten-rich layer is positively correlated with the overall number ratio of titanium atoms to tungsten atoms in the titanium-tungsten alloy coating.
[0015] Preferably, when the overall ratio of the number of titanium atoms to tungsten atoms in the titanium-tungsten alloy coating is 3:1, the thickness of the titanium-rich layer is greater than the thickness of the tungsten-rich layer; when the overall ratio of the number of titanium atoms to tungsten atoms in the titanium-tungsten alloy coating is 1:1, the thickness of the titanium-rich layer is less than the thickness of the tungsten-rich layer.
[0016] Preferably, the total thickness of the titanium-tungsten alloy coating is 50-500 nm.
[0017] The present invention also provides a method for preparing a negative electrode-free sodium ion battery current collector, which is used to prepare the negative electrode-free sodium ion battery current collector as described above, comprising: using a magnetron sputtering or plasma enhanced chemical vapor deposition process to prepare a titanium-tungsten alloy coating with a gradient component distribution on the surface of an aluminum foil substrate.
[0018] The present invention also provides a negative electrode-free sodium ion battery, which uses the above-mentioned negative electrode-free sodium ion battery current collector as the negative electrode current collector.
[0019] The present invention also provides a method for preparing a negative electrode-free sodium ion battery, which is used to prepare the negative electrode-free sodium ion battery as described above, comprising: step S1, using an aluminum foil substrate coated with a titanium-tungsten alloy coating as a negative electrode current collector, and assembling it with a sodium metal positive electrode or a sodium compensation positive electrode and an electrolyte to form a negative electrode-free sodium ion battery; step S2, charging the negative electrode-free sodium ion battery, during the first charging, sodium ions are released from the positive electrode, preferentially nucleated on the surface of the titanium-tungsten alloy coating and deposited as a dense metallic sodium layer, forming a negative electrode-free structure.
[0020] The above technical solution has the following advantages or beneficial effects: 1. By coating a titanium-tungsten alloy coating on the surface of the aluminum foil substrate, and the coating has a gradient component distribution, the synergistic effect of titanium and tungsten is used to regulate the electron distribution on the alloy surface, forming a highly sodium-affinity active site, significantly reducing the sodium nucleation overpotential, and inducing dense, dendrite-free sodium deposition behavior. This solves the problem of low surface energy of the traditional aluminum foil current collector, which leads to uneven sodium ion deposition.
[0021] 2. Use magnetron sputtering or plasma enhanced chemical vapor deposition (PECVD) technology to prepare a titanium-tungsten alloy coating on the surface of the aluminum foil substrate. This low-temperature deposition process can avoid thermal deformation of the aluminum foil substrate while ensuring the compactness and low defect density of the alloy coating. A battery current collector suitable for negative-electrode-free sodium-ion batteries can be obtained by efficiently and stably preparing a titanium-tungsten alloy coating on the surface of the aluminum foil substrate.
[0022] 3. In the negative electrode-free sodium ion battery, aluminum foil with a titanium-tungsten alloy gradient coating is used as the negative electrode current collector. This coating solves the problems of sodium nucleation uniformity, volume stability and interface compatibility through its unique physicochemical properties (such as high sodium affinity, high modulus, low volume expansion rate and excellent chemical inertness), thereby improving the cycle life and safety of the negative electrode-free sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a schematic diagram of the structure of a titanium-tungsten alloy coating in a preferred embodiment of the present invention; Figure 2 The present invention is a schematic flow chart of a method for preparing a negative electrode-free sodium ion battery in a preferred embodiment of the present invention. DETAILED DESCRIPTION
[0024] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The present invention is not limited to this embodiment, and other embodiments may also fall within the scope of the present invention as long as they conform to the gist of the present invention.
[0025] In a preferred embodiment of the present invention, based on the above-mentioned problems existing in the prior art, a negative electrode-free sodium ion battery current collector based on a titanium-tungsten alloy gradient coating is provided, comprising: an aluminum foil substrate, and a titanium-tungsten alloy coating coated on the surface of the aluminum foil substrate, wherein the titanium-tungsten alloy coating has a gradient component distribution.
[0026] Specifically, in this embodiment, a core structure of a battery current collector is defined, that is, a titanium-tungsten alloy gradient coating is coated on the surface of an aluminum foil substrate, wherein the beneficial effects of the titanium-tungsten alloy and the gradient distribution are: 1. Beneficial effects of coating 1.1 High sodium affinity: Technical principle: The weak adsorption of titanium (Ti) and sodium (Na) and the high electronic conductivity of tungsten (W) synergistically regulate the interfacial electron distribution.
[0027] Beneficial effects: This highly sodium-affinity active site can guide the uniform deposition of sodium ions and effectively inhibit dendrite growth, thereby improving the safety and cycle stability of the battery.
[0028] 1.2 Excellent mechanical stability: Technical principle: Titanium tungsten alloy has high modulus (>200 GPa) and low thermal expansion coefficient (<6×10 -6 / K), which can withstand the mechanical stress during the sodium deposition / stripping process.
[0029] Beneficial effects: The coating volume change rate is <5% (much lower than the >200% of traditional Na-Al alloy), which avoids the pulverization of the interface structure, maintains the stability of the interface electrical contact, and significantly improves the cycle life of the battery.
[0030] 1.3 Good chemical stability: Technical principle: Titanium-tungsten alloy has excellent chemical inertness in a wide voltage range (0-5V vs. Na+ / Na), and can resist corrosion from sodium metal and decomposition products of electrolyte.
[0031] Beneficial effects: Ensure the dynamic balance of interface impedance during long cycles, reduce interface side reactions, and improve the coulombic efficiency and cycle stability of the battery.
[0032] 1.4 Dynamic passivation layer protection: Technical principle: The surface of titanium-tungsten alloy spontaneously forms a dense TiO2-WO3 composite passivation layer during the cycle, and its high ionic conductivity (>10 -4 S / cm) and dynamic self-healing ability effectively inhibit the decomposition of the electrolyte.
[0033] Beneficial effects: The passivation layer can block the corrosion of the interface by the decomposition products of the electrolyte (such as Na2CO3), further improving the chemical stability and cycle life of the battery.
[0034] 2. Beneficial effects of gradient 2.1 Enhance bonding strength: Design principle: The coating forms a gradient component distribution from the bottom layer to the surface, and the bottom layer is a titanium-rich layer to enhance the bonding strength with the aluminum foil.
[0035] Beneficial effects: This gradient design can ensure a close bond between the coating and the aluminum foil substrate, preventing the coating from falling off or powdering during cycling, and improving the reliability and durability of the battery.
[0036] 2.2 Improve electrical conductivity and chemical stability: Design principle: The surface layer is a tungsten-rich layer to improve conductivity and chemical stability.
[0037] Beneficial effects: The high conductivity of the tungsten-rich layer can reduce the internal resistance of the battery and improve the battery's charge and discharge efficiency; at the same time, its excellent chemical stability can further protect the battery from electrolyte corrosion and extend the battery's service life.
[0038] In a preferred embodiment of the present invention, Figure 1 As shown, the titanium-tungsten alloy coating includes a titanium-rich layer 2, a transition layer 3 and a tungsten-rich layer 4 stacked in sequence from an aluminum foil substrate 1 to the outside; the ratio of titanium atoms to tungsten atoms in the titanium-rich layer, the transition layer and the tungsten-rich layer decreases in sequence to form a gradient component distribution.
[0039] Specifically, the effects of providing the titanium-rich layer, the transition layer and the tungsten-rich layer in this embodiment are as follows: Titanium-rich layer: directly in contact with the aluminum foil substrate, with a high titanium (Ti) content (such as Ti:W≈3:1). The high affinity between titanium and aluminum (low Al-Ti interface energy) is used to enhance the bonding between the coating and the aluminum foil to avoid peeling.
[0040] Transition layer: located between the titanium-rich layer and the tungsten-rich layer, the composition changes continuously from titanium-rich to tungsten-rich (such as Ti:W gradually transitioning from 3:1 to 1:1). The composition gradient is achieved by dynamically controlling the target power or gas ratio in the magnetron sputtering process to ensure a smooth transition between the layers.
[0041] Tungsten-rich layer: The outermost layer has a high tungsten (W) content (e.g. Ti:W≈1:1). It uses the high conductivity of tungsten (resistivity≈5.6×10 -8 Ω·m) and chemical inertness (resistant to sodium metal corrosion), optimizing the sodium ion deposition interface.
[0042] The titanium-rich layer, transition layer and tungsten-rich layer have the following beneficial effects: 1. Enhanced bonding strength: The titanium-rich layer is in direct contact with the aluminum foil substrate. Due to the high affinity between titanium and aluminum, the bonding strength between the coating and the aluminum foil is significantly enhanced. This close bonding can effectively prevent the coating from peeling or powdering during the battery cycle, and improve the reliability and durability of the battery.
[0043] 2. Optimize conductivity and chemical stability: As the coating transitions from a titanium-rich layer to a tungsten-rich layer, the tungsten content gradually increases, and the conductivity of the coating also increases. The high conductivity of the tungsten-rich layer can significantly reduce the internal resistance of the battery and improve the battery's charge and discharge efficiency.
[0044] 3. Chemical stability: The high chemical inertness of the tungsten-rich layer enables it to resist corrosion from sodium metal and decomposition products of the electrolyte, thereby protecting the battery from the electrolyte and extending the battery life.
[0045] 4. Inducing uniform sodium deposition: Due to the weak adsorption of titanium and sodium and the high electronic conductivity of tungsten, the titanium-tungsten alloy coating can form active sites with low nucleation barriers, guiding the uniform deposition of sodium ions. This uniform sodium deposition behavior can effectively inhibit dendrite growth and improve the safety and cycle stability of the battery.
[0046] 5. Inhibit volume expansion: Titanium-tungsten alloy has high modulus and low volume expansion rate (<5%), and can withstand the mechanical stress during sodium deposition / stripping. This excellent mechanical stability can effectively inhibit the volume expansion of the coating during the cycle, avoid interface structure powdering, and maintain interface electrical contact stability.
[0047] 6. Dynamic passivation layer protection: During the battery cycle, a dense TiO2-WO3 composite passivation layer will spontaneously form on the surface of the titanium-tungsten alloy. This passivation layer has high ionic conductivity and dynamic self-repairing ability, which can effectively inhibit the decomposition of the electrolyte, block the corrosion of the interface by the decomposition products of the electrolyte, and further improve the chemical stability and cycle life of the battery.
[0048] 7. Flexible adjustment of overall performance: By adjusting the ratio and thickness of titanium atoms and tungsten atoms in the titanium-rich layer, transition layer and tungsten-rich layer, the overall performance of the coating can be flexibly controlled. For example, increasing the thickness of the titanium-rich layer can enhance the bonding force; increasing the thickness of the tungsten-rich layer can improve the conductivity and chemical stability. This flexible design enables the coating to be customized and optimized according to the needs of different application scenarios.
[0049] In summary, the gradient component distribution of the titanium-tungsten alloy coating in the present invention achieves performance improvements in many aspects such as bonding strength, conductivity, chemical stability, sodium deposition uniformity, volume expansion inhibition, and dynamic passivation layer protection through the reasonable design of the titanium-rich layer, the transition layer, and the tungsten-rich layer, providing an efficient and reliable solution for the design of the current collector of the negative electrode-free sodium ion battery.
[0050] In a preferred embodiment of the present invention, the titanium-rich layer contains titanium atoms and tungsten atoms in a first ratio.
[0051] In a preferred embodiment of the present invention, the tungsten-rich layer contains titanium atoms and tungsten atoms in a second ratio.
[0052] In a preferred embodiment of the present invention, the transition layer includes titanium atoms and tungsten atoms that change continuously and gradually from a first ratio to a second ratio.
[0053] Specifically, in this embodiment, the first ratio is preferably set to Ti:W=3:1, and the second ratio is preferably set to Ti:W=1:1; in a preferred embodiment of the present invention, the transition layer includes multiple subdivision layers, and the number ratio of titanium atoms and tungsten atoms in the subdivision layers gradually changes from 3:1 to 1:1 in levels.
[0054] In a preferred embodiment of the present invention, the atomic number ratio of the overall titanium atoms to the tungsten atoms in the titanium-tungsten alloy coating is in the range of 1:1 to 3:1.
[0055] In a preferred embodiment of the present invention, the ratio of the thickness of the titanium-rich layer to the thickness of the tungsten-rich layer is positively correlated with the overall number ratio of titanium atoms to tungsten atoms in the titanium-tungsten alloy coating.
[0056] In a preferred embodiment of the present invention, when the ratio of the number of titanium atoms to tungsten atoms in the titanium-tungsten alloy coating is 3:1, the thickness of the titanium-rich layer is greater than the thickness of the tungsten-rich layer.
[0057] Preferably, when the ratio of the number of titanium atoms to tungsten atoms in the titanium-tungsten alloy coating is 1:1, the thickness of the titanium-rich layer is less than the thickness of the tungsten-rich layer.
[0058] The atomic ratio range (1:1 to 3:1) is the average ratio of the entire coating. The atomic ratio of each layer in the gradient structure is designed differently according to functional requirements: When the overall atomic ratio is 3:1 (Ti:W): the bottom layer accounts for a larger proportion (e.g. the bottom layer thickness accounts for 70%, Ti:W=3:1; the surface layer accounts for 30%, Ti:W=1:1), and the overall average is 3:1.
[0059] When the overall atomic ratio is 1:1 (Ti:W): the bottom layer accounts for a smaller proportion (for example, the bottom layer thickness accounts for 30%, Ti:W=3:1; the surface layer accounts for 70%, Ti:W=1:1), and the overall average is 1:1.
[0060] Key point: The bottom layer of the gradient structure is always a titanium-rich layer (Ti:W≈3:1), and the surface layer is always a tungsten-rich layer (Ti:W≈1:1). The overall atomic ratio is adjusted only by the thickness ratio of each layer to ensure that the functional stratification remains unchanged.
[0061] In a preferred embodiment of the present invention, the total thickness of the titanium-tungsten alloy coating is 50-500 nm. The total coating thickness (50-500 nm) is achieved by adjusting the thickness ratio of each gradient layer, and the relationship with the atomic ratio and the hierarchical distribution is as follows: In one embodiment, the total thickness is 50 nm (very thin coating) Bottom layer (Ti-rich layer): 20 nm, Ti:W=3:1 Intermediate transition layer: 15 nm, Ti:W from 3:1→1:1 (or a ratio close to 1:1) Surface layer (tungsten-rich layer): 15 nm, Ti:W=1:1 The overall atomic ratio is ≈2:1 (the deposition rate of each layer is controlled by the sputtering time).
[0062] In another embodiment, the total thickness is 500 nm (thicker coating) In this embodiment, the transition layer includes a plurality of subdivided layers, and the ratio of titanium atoms to tungsten atoms in the subdivided layers gradually changes from a first ratio to a second ratio in a hierarchical manner.
[0063] Bottom layer (Ti-rich layer): 200 nm, Ti:W=3:1 Intermediate transition layer: 200 nm, Ti:W from 3:1→1:1 (subdivided into 10 layers, each layer 20 nm, composition gradient) Surface layer (tungsten-rich layer): 100 nm, Ti:W=1:1 The overall atomic ratio is ≈2:1 (fine gradients are achieved through a multi-layer sputtering process).
[0064] Correspondence summary: Atomic ratio control: The overall atomic ratio is adjusted by the thickness ratio of each layer, and the local ratio of titanium-rich bottom layer (Ti:W=3:1) and tungsten-rich surface layer (Ti:W=1:1) is fixed.
[0065] Thickness influence: Thin coating (50 nm): fewer gradient transition layers and steeper composition changes, suitable for high-magnification scenarios (reducing ion diffusion paths).
[0066] Thick coating (500 nm): The gradient transition is smoother and the components are subdivided into nano-scale multilayers, which is suitable for long-cycle requirements (relieving mechanical stress).
[0067] In order to illustrate the beneficial effects of the titanium-tungsten alloy coating of the present invention, two additional comparative examples are added for comparison: Example 1 mentioned above: a titanium-tungsten alloy coating with a total thickness of 50 nm is coated on an aluminum foil substrate; Example 2 mentioned above: a titanium-tungsten alloy coating with a total thickness of 500 nm is coated on an aluminum foil substrate; Comparative Example 1: ordinary aluminum foil is used as a negative electrode-free battery current collector; aluminum foil specification: aluminum foil thickness 12 nm; Comparative Example 2: carbon-coated aluminum foil is used as a negative electrode-free battery current collector; aluminum foil specification: aluminum foil thickness 12 nm, carbon coating thickness 1 nm; Example 1, Example 2, Comparative Example 1, and Comparative Example 2 are subjected to rate test, cycle capacity retention test, and coulomb efficiency test using the same test experimental process, and the experimental results are shown in Table 1: 1. Rate test plan: 1.1, Charge at 0.5C current to the upper cut-off voltage; leave for 30 minutes; 1.2, 0.2C current discharge to the lower limit cut-off voltage, record the capacity C0; leave it for 30 minutes; 1.3, 0.5C current charging to the upper limit cut-off voltage; leave for 30 minutes; 1.4, discharge with 1C current to the lower cut-off voltage, and record the capacity C1; 1.5. Calculate the rate retention rate: (C1 / C0*100%).
[0068] 2. Cycle test plan: 2.1. Charge at 1.0C current to the upper cut-off voltage; leave for 30 minutes; 2.2, 1.0C current discharge to the lower limit cut-off voltage; leave for 30 minutes; 2.3. Repeat the above steps for 200 cycles; record the capacity of the first cycle C1, and the capacity of the 200th cycle C200; 2.4. Calculate the cycle capacity retention rate: (C200 / C1*100%).
[0069] 3. Coulomb efficiency is obtained by calculating the ratio of discharge capacity to charge capacity in one cycle.
[0070] Table 1 Comparison table of experimental results
[0071] Table 2 200 cycles 1.0C / 1.0C cycle capacity retention test results
[0072] For Example 1, the coating thickness of the 50nm titanium-tungsten alloy coating was measured to be 52nm after 200 charging cycles, and the coating thickness increased by 2nm, which is approximately equal to 4% (volume change rate <5%), which can solve the problem of drastic volume expansion caused by alloying modification.
[0073] The following conclusions can be drawn from the above experimental results comparison table: 1. Performance advantages of titanium-tungsten alloy coating vs. aluminum foil current collector The battery current collector with titanium-tungsten alloy coating has high rate retention (>97%) and high capacity retention (>90%) and Coulombic efficiency >99.5%, while the existing ordinary aluminum foil current collector has low rate retention (<90%), low capacity retention (<55%), and Coulombic efficiency of only 94.0~99.0%.
[0074] Titanium-tungsten alloy coating achieves the following through gradient atomic ratio design (Ti:W from 3:1→1:1): High-magnification scene adaptation: The steep gradient of the thin coating (50 nm) shortens the ion diffusion path; Long-cycle requirements are met: Gentle gradients of thick coatings (500 nm) disperse mechanical stresses.
[0075] 2. Effect of coating thickness on performance Thin coating: by reducing the number of transition layers (such as only 3 layers in Example 1), the ion diffusion path is short, the rate retention rate is 99.02%, and fast charging and discharging are preferentially supported; Thick coating: subdivided into 10 layers to achieve nanoscale gradient, mechanical stress dispersion, capacity retention rate of 92.38%, taking into account both cycle life and capacity attenuation.
[0076] 3. Performance difference analysis of comparison groups Comparative Example 1 (ordinary aluminum foil): without coating protection, oxidation of the aluminum foil leads to increased interface impedance and rapid capacity decay (25.42%); Comparative Example 2 (carbon-coated aluminum foil): The carbon coating (1 nm) partially alleviates oxidation, but the Coulomb efficiency (97.0-99.0%) is still lower than that of the titanium-tungsten coating; Example 1 / 2: The corrosion resistance of Ti-W alloy (especially the titanium-rich layer) significantly improves the interface stability, and the coulombic efficiency is >99.5%.
[0077] 4. Final Conclusion The gradient atomic ratio design and thickness optimization of the titanium-tungsten alloy coating significantly improve the comprehensive performance of the battery under high-rate scenarios and long-cycle requirements. Comparative experimental verification shows that the coating is superior to traditional aluminum foil current collectors in terms of rate retention, capacity retention, and coulombic efficiency, demonstrating its potential application value in the next generation of battery technology.
[0078] The present invention solves the core problems of drastic volume expansion caused by alloying modification (volume change rate reduced from >200% to <5%) and interface side reaction between sodium metal and electrolyte (Coulomb efficiency increased to >99.5%) through the design of titanium-tungsten (Ti-W) alloy gradient coating. At the same time, the low-temperature deposition process avoids thermal deformation of the aluminum foil substrate, and the gradient structure enhances the adhesion and corrosion resistance of the coating, adapting to the liquid / solid system, significantly improving the battery cycle life (capacity retention rate >90% for 200 times) and safety.
[0079] The present invention also provides a method for preparing a negative electrode-free sodium ion battery current collector, which is used to prepare the above negative electrode-free sodium ion battery current collector, comprising: using a magnetron sputtering or plasma enhanced chemical vapor deposition process to form a titanium-tungsten alloy coating on the surface of an aluminum foil substrate.
[0080] Specifically, in this embodiment, a titanium-tungsten alloy coating is formed on the surface of an aluminum foil substrate by magnetron sputtering or plasma enhanced chemical vapor deposition process, which is used to prepare a negative electrode-free sodium ion battery current collector, and has significant advantages.
[0081] Process advantages High-quality coating: Both magnetron sputtering and plasma enhanced chemical vapor deposition (PECVD) techniques can produce dense, uniform and highly adhesive titanium-tungsten alloy coatings. This coating has good conductivity and chemical stability, making it suitable as a current collector for anode-free sodium-ion batteries.
[0082] Low-temperature deposition: PECVD technology enables high-quality thin film deposition at lower temperatures, which helps protect the aluminum foil substrate from high-temperature damage while reducing energy consumption.
[0083] Strong controllability: By adjusting process parameters such as sputtering power, gas flow, deposition temperature, etc., the composition, structure and thickness of the coating can be precisely controlled to meet different application requirements.
[0084] Environmentally friendly and pollution-free: Both magnetron sputtering and PECVD technologies are dry processes that do not produce waste liquid, waste residue and other pollutants, and meet environmental protection requirements.
[0085] The following are two embodiments, one of which is particularly directed to a transition layer including a plurality of subdivided layers.
[0086] Example 1: Preparation of a titanium-tungsten alloy coating with 10 subdivided gradient transition layers by multi-layer sputtering process In a preferred embodiment of the present invention, the titanium-tungsten alloy coating is designed as a three-layer structure, including a bottom layer, an intermediate transition layer and a surface layer. The bottom layer is a titanium-rich layer, the surface layer is a tungsten-rich layer, and the intermediate transition layer is a 10-layer subdivision structure, each layer is 20 nm thick, and the ratio of titanium atoms to tungsten atoms gradually transitions from 3:1 in the titanium-rich layer to 1:1 in the tungsten-rich layer. The total thickness of the coating is 500 nm.
[0087] The specific implementation steps included in this example are as follows: Substrate pretreatment: Clean and dry the aluminum foil substrate to ensure that there is no impurities such as oil, oxides, etc. on the surface.
[0088] Multilayer sputtering coating: Bottom layer (titanium-rich layer): A titanium-rich layer with a thickness of 200 nm and an atomic ratio of Ti:W = 3:1 is deposited on the aluminum foil substrate using a magnetron sputtering process.
[0089] This layer serves as a base for the coating, providing good adhesion and initial conductivity.
[0090] Intermediate transition layer (10-layer subdivision structure): The transition layer is designed to have a 10-layer structure, with each layer being 20 nm thick and a total thickness of 200 nm.
[0091] Layer 1 (close to the bottom layer): atomic ratio Ti:W=3:1, the same as the bottom layer.
[0092] Second layer: The atomic ratio begins to gradually decrease the proportion of titanium, such as Ti:W=2.8:1.
[0093] Layer 3: Continue to reduce the proportion of titanium, such as Ti:W=2.6:1.
[0094] And so on, the proportion of titanium in each layer gradually decreases until the 10th layer.
[0095] The 10th layer (near the surface): atomic ratio Ti:W = 1:1, the same as the surface layer.
[0096] By precisely controlling the sputtering process parameters, a smooth transition of each layer's components can be achieved.
[0097] Surface layer (tungsten-rich layer): A tungsten-rich layer with a thickness of 100 nm and an atomic ratio of Ti:W=1:1 is deposited on the transition layer.
[0098] This layer provides excellent electrical conductivity and chemical stability as the final surface of the coating.
[0099] Specific examples: The total thickness of the coating is 500 nm, consisting of a base layer, 10 transition layers and a surface layer.
[0100] The bottom layer is a titanium-rich layer with a thickness of 200 nm and Ti:W=3:1.
[0101] The transition layer is a 10-layer subdivision structure, each layer is 20 nm, the total thickness is 200 nm, and the atomic ratio gradually transitions from Ti:W=3:1 to 1:1.
[0102] The surface layer is a tungsten-rich layer with a thickness of 100 nm and Ti:W=1:1.
[0103] Sputtering process control: By precisely controlling parameters such as sputtering time, sputtering power and gas flow rate, precise control of the thickness of each layer and gradual change of the composition can be achieved.
[0104] Multilayer sputtering equipment is used to ensure smooth transitions between layers and uniform changes in composition.
[0105] Post-treatment: The coated aluminum foil substrate is annealed to improve the crystallinity and overall performance of the coating.
[0106] Key point: The coating is designed as a three-layer structure, including a base layer, 10 subdivided transition layers and a surface layer.
[0107] The ratio of titanium atoms to tungsten atoms in the transition layer changes gradually from a titanium-rich layer to a tungsten-rich layer in order to achieve a smooth transition of the components.
[0108] By precisely controlling the sputtering process parameters, optimized performance and customized design of the coating can be achieved.
[0109] In this embodiment, a titanium-tungsten alloy coating having 10 subdivided gradient transition layers is prepared by a multilayer sputtering process, which meets the requirements of specific applications for coating performance and component gradient, and is suitable for the preparation of a negative electrode-free sodium ion battery current collector.
[0110] Example 2: Preparation method of negative electrode-free sodium ion battery current collector based on PECVD technology This embodiment is for an ultra-thin titanium-tungsten alloy coating with a total thickness of 50 nm. The coating is designed as a three-layer structure: the bottom layer (titanium-rich layer) is 20 nm, Ti:W=3:1; the intermediate transition layer is 15 nm, Ti:W gradually changes from 3:1 to 1.5:1; the surface layer (tungsten-rich layer) is 15nm, Ti:W=1:1. The overall coating atomic ratio is about 2:1, and the deposition rate of each layer is regulated by controlling the sputtering (here PECVD deposition) time. The present invention provides a method for preparing the titanium-tungsten alloy coating on the surface of an aluminum foil substrate using a plasma enhanced chemical vapor deposition (PECVD) process, which is used to prepare a negative electrode-free sodium ion battery current collector.
[0111] The specific implementation steps included in this example are as follows: 1. Preparation of aluminum foil substrate: Choose aluminum foil with a smooth surface, no oil stains, and no oxides as the substrate.
[0112] Wash and dry the aluminum foil to ensure the substrate surface is clean to improve the adhesion of the coating.
[0113] 2. PECVD equipment settings: Check and confirm that the vacuum system, gas supply system, plasma generation system, etc. of the PECVD equipment are in good working condition.
[0114] Set the deposition chamber temperature to an appropriate range to ensure the stability of the deposition process and the coating quality.
[0115] 3. Titanium tungsten alloy coating deposition: 3.1 Bottom layer (Titanium-rich layer) deposition: Precursor gases containing titanium and tungsten, such as titanium tetrachloride (TiCl4) and tungsten hexafluoride (WF6), and reactive gases (such as hydrogen H2 as a reducing gas and argon Ar as a carrier gas) are introduced.
[0116] The gas flow ratio was adjusted so that the atomic ratio of the deposited coating reached Ti:W=3:1.
[0117] The plasma generator is turned on to generate plasma to promote the chemical reaction and deposition of the precursor gas.
[0118] By precisely controlling the deposition time, the bottom layer thickness was ensured to be 20 nm.
[0119] 3.2 Intermediate transition layer deposition: The flow ratio of the precursor gas was gradually adjusted so that the atomic ratio of the deposited coating gradually transitioned from Ti:W=3:1 to 1.5:1.
[0120] Use programmed control or manually adjust the gas flow ratio step by step to achieve a smooth transition of components.
[0121] Keep the plasma generator on to ensure stable deposition conditions.
[0122] By precisely controlling the deposition time, the thickness of the transition layer was ensured to be 15 nm.
[0123] 3.3 Surface layer (tungsten-rich layer) deposition: The flow ratio of the precursor gas was adjusted so that the atomic ratio of the deposited coating reached Ti:W=1:1.
[0124] Keep the plasma generator on to ensure a stable deposition process.
[0125] By precisely controlling the deposition time, the surface layer thickness was ensured to be 15 nm.
[0126] 4. Post-treatment of coating: Turn off the plasma generator and stop the gas supply.
[0127] The deposition chamber was evacuated to a vacuum state and then cooled to room temperature.
[0128] Remove the coating sample and perform necessary cleaning and drying to remove any remaining deposits or reaction by-products.
[0129] Key Points: A titanium-tungsten alloy coating with a total thickness of 50 nm was accurately prepared on the surface of an aluminum foil substrate using the PECVD process.
[0130] The coating is designed as a three-layer structure, and the thickness and composition of each layer meet the design requirements, achieving a smooth transition of components.
[0131] By precisely controlling the deposition time and gas flow ratio, precise control of the overall atomic ratio of the coating of approximately 2:1 was achieved.
[0132] The prepared negative electrode-free sodium ion battery current collector has excellent conductivity and sodium ion insertion / extraction performance, meeting the application requirements of sodium ion batteries.
[0133] This embodiment successfully prepared a negative electrode-free sodium ion battery current collector with a titanium-tungsten alloy coating having a specific structure through the PECVD process, providing strong technical support for the research and development and application of sodium ion batteries.
[0134] The present invention also provides a negative electrode-free sodium ion battery, which adopts the negative electrode-free sodium ion battery current collector as the negative electrode current collector.
[0135] The present invention also provides a method for preparing a negative electrode-free sodium ion battery, which is used to prepare the negative electrode-free sodium ion battery as described above. Figure 2 As shown, it includes: step S1, using an aluminum foil substrate coated with a titanium-tungsten alloy coating as a negative electrode current collector, and assembling it with a sodium metal positive electrode or a sodium compensation positive electrode and an electrolyte to form a negative electrode-free sodium ion battery; step S2, charging the negative electrode-free sodium ion battery. During the first charging, sodium ions are released from the positive electrode, preferentially nucleated on the surface of the titanium-tungsten alloy coating and deposited as a dense metallic sodium layer, forming a negative electrode-free structure.
[0136] Specifically, the negative electrode-free sodium ion battery uses the negative electrode-free sodium ion battery current collector as the negative electrode current collector, which has the following advantages: Dynamic protection of in-situ passivation layer: A dense TiO2-WO3 composite passivation layer is formed on the surface of the titanium-tungsten alloy during the charging cycle, blocking the corrosion of the interface by the decomposition products of the electrolyte (such as Na2CO3).
[0137] High mechanical robustness: The high modulus and low expansion properties of titanium-tungsten alloy ensure the integrity of the coating structure during sodium deposition / stripping, and the coating is crack-free after 100 cycles (SEM verification). Charge and discharge cycles were performed at 0.5-3 C rates to monitor the sodium deposition morphology (SEM), interfacial impedance (EIS) and cycle life (capacity retention).
[0138] Full system adaptability: The coating is compatible with liquid and solid electrolyte systems, and exhibits stable performance under high-voltage positive electrodes (such as O3-type layered oxides) and a wide temperature range (-20~60°C).
[0139] Traditional aluminum foil current collectors have a high sodium nucleation barrier (>100 mV) due to their low surface energy, and although existing alloying coatings (such as Al-Sn) can reduce the overpotential, the alloying reaction is accompanied by a violent volume expansion (>200%), which causes interface pulverization and capacity decay. The present invention constructs a gradient titanium-tungsten alloy coating on the surface of aluminum foil (the bottom layer is rich in titanium to enhance the bonding strength, and the surface layer is rich in tungsten to enhance the conductivity) by regulating the atomic ratio of titanium and tungsten (1:1 to 3:1) and combining it with a magnetron sputtering low-temperature deposition process (150-300°C), while simultaneously achieving near-zero volume expansion (<5%) and high chemical inertness. A nanoscale TiO2-WO3 composite passivation layer (5-10 nm thick) is spontaneously formed on the surface of the titanium-tungsten alloy during the cycle, and its high ionic conductivity (>10 -4 S / cm) and dynamic self-healing ability effectively inhibit electrolyte decomposition (Coulomb efficiency>99.5%) and dendrite growth (deposition layer porosity<5%). In addition, the high modulus (>200 GPa) and low thermal expansion coefficient (<6×10 -6 / K) endows the coating with excellent mechanical robustness, which can adapt to liquid and solid electrolyte systems and maintain a stable interface (capacity retention rate >90% after 200 cycles) under high-voltage positive electrodes (>4 V) and a wide temperature range (-20~60°C). Through the collaborative innovation of material components, processes and interface design, this technology provides a highly compatible and long-life current collector solution for the industrialization of negative-electrode-free sodium batteries.
[0140] The above are only preferred embodiments of the present invention, and are not intended to limit the implementation methods and protection scope of the present invention. Those skilled in the art should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the contents of this specification and illustrations should be included in the protection scope of the present invention.
Claims
1. A battery current collector, characterized in that: include: An aluminum foil substrate and a titanium-tungsten alloy coating coated on the surface of the aluminum foil substrate, wherein the titanium-tungsten alloy coating has a gradient component distribution.
2. The battery current collector according to claim 1, characterized in that: The titanium-tungsten alloy coating comprises a titanium-rich layer, a transition layer and a tungsten-rich layer stacked in sequence from an aluminum foil substrate outward; the number ratios of titanium atoms and tungsten atoms in the titanium-rich layer, the transition layer and the tungsten-rich layer decrease in sequence to form the gradient component distribution.
3. The battery current collector according to claim 2, characterized in that: The transition layer includes multiple subdivided layers, and the ratio of the number of titanium atoms and tungsten atoms in the subdivided layers gradually changes from 3:1 to 1:1 in levels.
4. The battery current collector according to claim 2, characterized in that: The ratio of the number of titanium atoms to that of tungsten atoms in the titanium-tungsten alloy coating is in the range of 1:1 to 3:
1.
5. The battery current collector according to claim 4, characterized in that: The ratio of the thickness of the titanium-rich layer to the thickness of the tungsten-rich layer is positively correlated with the number ratio of the overall titanium atoms and tungsten atoms in the titanium-tungsten alloy coating.
6. The battery current collector according to claim 5, characterized in that: When the overall ratio of the number of titanium atoms to tungsten atoms in the titanium-tungsten alloy coating is 3:1, the thickness of the titanium-rich layer is greater than the thickness of the tungsten-rich layer; when the overall ratio of the number of titanium atoms to tungsten atoms in the titanium-tungsten alloy coating is 1:1, the thickness of the titanium-rich layer is less than the thickness of the tungsten-rich layer.
7. The battery current collector according to claim 1, characterized in that: The total thickness of the titanium-tungsten alloy coating is 50-500 nm.
8. A method for preparing a battery current collector, characterized in that: The method for preparing the battery current collector as claimed in any one of claims 1 to 7 comprises: using magnetron sputtering or plasma enhanced chemical vapor deposition technology to prepare a titanium-tungsten alloy coating with a gradient component distribution on the surface of an aluminum foil substrate.
9. A negative electrode-free sodium ion battery, characterized in that: The battery current collector described in any one of 1-7 is used as the negative electrode current collector.
10. A method for preparing a negative electrode-free sodium ion battery, characterized in that: The method for preparing a negative electrode-free sodium ion battery as claimed in claim 9 comprises: step S1, using the battery current collector obtained from an aluminum foil substrate coated with a titanium tungsten alloy coating as a negative electrode current collector, and assembling it with a sodium metal positive electrode or a sodium compensation positive electrode, and an electrolyte into a negative electrode-free sodium ion battery; step S2, charging the negative electrode-free sodium ion battery, during the first charging, sodium ions are released from the positive electrode, preferentially nucleate on the surface of the titanium tungsten alloy coating and deposited as a dense metallic sodium layer, forming a negative electrode-free structure.
Citation Information
Patent Citations
Current collector and electrode
CN113036154A
Gradient potential distribution positive electrode, a lithium ion battery and a preparation method and application of the lithium ion battery
CN113113567A
Lithium metal battery negative electrode material, preparation method thereof and lithium metal battery
CN114784259A
Lithium / sodium ion battery negative electrode with double-gradient structure and preparation method of lithium / sodium ion battery negative electrode
CN115732631A
Composite current collector of negative-electrode-free sodium metal battery and preparation method of composite current collector
CN117317239A
Cited By
Preparation process and application of current collector of negative-electrode-free sodium-ion battery
CN121394417A